Engineering fracture assessment of FV520B steel impeller subjected to dynamic loading. (September 2015) - Wu, Qiaoguo; Chen, Xuedong; Fan, Zhichao; Nie, Defu; Pan, Jianhua
Highlights: Fracture behavior of the FV520B steel under different loading rates was studied. A formula for calculating fracture toughness at different loading rate was proposed. J -integral histories and loading rates at crack tips of the impeller were evaluated. Dynamic failure assessment of the cracked impeller was conducted. Abstract: The dynamic fracture assessment method applied to a cracked centrifugal impeller subjected to dynamic loading is the focus of this study. J -integral histories and loading rates at crack tips were evaluated by numerical simulation through ABAQUS and Zencrack software. True stress–strain relations, fracture mechanism and fracture toughness of the impeller material FV520B steel were investigated over a wide range of loading rates by experimental and theoretical methods. Fracture assessment with consideration to rate effects was then conducted based on the CEGB R6 procedure. The present method demonstrated advantages over existing methods evaluated by an equivalent static load.